Perancangan Lengan Robot Sebagai Media Pembelajaran Programmable Logic Controller Di Laboratorium PLC Politeknik Kampar - Purnama Irwan; Romiyadi Romiyadi (Jurnal Rekayasa Proses dan Industri Terapan, 2024)
This research was done to meet the needs of the Laboratory of PLC in Politeknik Kampar will be a creative learning media and innovative. With a learning media in the form of a robot arm, the students are expected to be easier to understand and apply a control system using a Programmable Logic Controller (PLC). The research begins by making the design of the robot arm and then assembled into a coherent whole by adding stepper motors on each of the degrees of freedom. Once the tool is assembled, then testing by using PLC. Tests such as the degree rotation (DOF) of each of the robot arm to grab an object. The end result of this research is a tool in the form of a robotic arm that is ready for learning PLC in Politeknik Kampar.